2007
DOI: 10.1097/01.wnp.0000237075.85689.33
|View full text |Cite
|
Sign up to set email alerts
|

Motor Evoked Potentials After Transcranial Magnetic Stimulation Support Hypothesis of Coexisting Central Mechanism in Obstetric Brachial Palsy

Abstract: Six infants with obstetric brachial palsy, ranging from 4 to 7 months of age, were investigated. One was suspected of having extensive brachial plexus lesions and five were suspected of having a unilateral lesion of both roots C5 and C6. All were referred to our center to investigate the possibility for reconstructive surgery. In all infants, even at this age, transcranial magnetic stimulation resulted in motor evoked potentials (MEP) in the biceps (in one, in the brachioradial) muscles. Averaging could not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Our results suggest that infants with perinatal stroke display early differences in TMS elicited MEPs in the wrist flexors from the more and less-affected hemispheres. The phenomenon of absence of MEPs in the first year of life may be unique to perinatal stroke as infants with brachial plexus injury [27], epilepsy [28], and typically developing infants [6] displayed intact MEPs in the upper extremity musculature. As such, the absence of MEPs from the MAH could be a unique early biomarker of atypical neurodevelopment of the CST in infants with perinatal stroke at risk of CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that infants with perinatal stroke display early differences in TMS elicited MEPs in the wrist flexors from the more and less-affected hemispheres. The phenomenon of absence of MEPs in the first year of life may be unique to perinatal stroke as infants with brachial plexus injury [27], epilepsy [28], and typically developing infants [6] displayed intact MEPs in the upper extremity musculature. As such, the absence of MEPs from the MAH could be a unique early biomarker of atypical neurodevelopment of the CST in infants with perinatal stroke at risk of CP.…”
Section: Discussionmentioning
confidence: 99%
“…In the two infants in whom we were unable to record MEPs from either hemisphere, it is possible that the location targeted for stimulation was not the true anatomical area of M1 associated with motor control of the wrist flexors in those infants, and the assessment of the surrounding cortex was not completed in a wide enough radius. TMS assessment time and number of trials was limited by infant compliance and tolerance, and a comprehensive systematic evaluation of the cortical area of interest utilizing standard protocols implemented in older children and adults is not feasible in infants [24,27,38]. Given prior reports of motor thresholds being greatest within the first year of life, and higher in infants with perinatal stroke compared to typically developing infants [6], these two infants may have demonstrated a motor threshold which exceeded TMS intensities of 90% MSO, which was the highest intensity we utilized.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that, as in adults, all of the processes involved in the secondary lesion are variable, depending on the individual's genome and epigenome. Moreover, neonates have extra ("luxury") innervation to the muscles and skin of the upper limb (Blaauw et al, 2008;Colon et al, 2003Colon et al, , 2007Duval & Gullain, 1898;Vredeveld et al, 2000).…”
Section: Nbpp With and Without Shoulder Dystocia From A Comparative And Evolutionary Perspectivementioning
confidence: 99%
“…A subgroup of these patients has demonstrable MUs on EMG, but persistently impaired motor skills using these reinnervated muscles 99. Experimental studies have suggested that this may be due to a developmental apraxia, with defective motor programming early in infancy 100 101…”
Section: Rehabilitation and Non-surgical Approachesmentioning
confidence: 99%